ANALISIS PERTUMBUHAN EKONOMI REGIONAL SUMATERA BARAT (MODEL HARROD-DOMARD) - Eliza, Eliza (Jurnal Ekobistek, 2014)
Growth of economy was description about influence development policy was did especial of economy spacious in a region. Based result of research  was got with Harrold-Domard Model, value of average economy growth from spacious model was 5,8 % every year, whereas educator spacious  was 0,65%. This meaning still narrow opportunity of effort to get occupation for effect unemployment worker surplus or 9 > 9 to encourage the educator create  opportunity of effort Keyword: Harrod-Domard Models, Growth Economics, PDRB, Investment